Autoimmune diseases and pregnancy. Issue 6 (December 2019) - Tincani, Angela; Nalli, Cecilia; Khizroeva, Jamilya; Bitsadze, Victoria; Lojacono, Andrea; Andreoli, Laura; Shoenfeld, Yehuda; Makatsariya, Alexander
Abstract : Pregnancy in autoimmune diseases remains an argument of debate. In last years great improvements were done and with the correct medical support women with disease such as Systemic Lupus Erythematosus or Antiphospholipid Syndrome can afford a pregnancy and have healthy babies. The starting point is a good counselling. Women should be informed about risks that can occur taking some medications while pregnant and, on the other hand, that there are medications that can be safety assumed during pregnancy. Furthermore, there are known maternal risks factor such as the presence of antiphospholipid antibodies or anti-Ro/SSA antibodies that must be carefully manage by both rheumatologists and obstetrics. In addition, also disease activity during pregnancy can represent an issue. For all these reason, a multidisciplinary approach is mandatory in order to give our patients an optimal medical support, before, during and after pregnancy.